Ultrasound-assisted rapid extraction of bacterial polyhydroxyalkanoates and its blend film morphology / Khairul Anwar Bin Ishak - Ishak, Khairul Anwar (2014)
Medium-chain-length polyhydroxyalkanoate (mcl-PHA) is biodegradable polyester that gained serious attention recently, mainly because of its versatility to accomodate a wide range of applications especially in biomedical area. Like other biopolyesters in PHA family, it is synthesized intracellularly by microorganisms under nutrient stress condition i.e abundant carbon sources than other essential nutrients like nitrogen, oxygen, sulphur, etc. It functions as carbon and energy storage to the cells during depletion of carbon sources. A well known group of bacteria able to specifically produce mcl-PHA is fluorescent pseudomonads belonging to rRNA homology group 1. To make industrial production of mcl-PHA viable, significant efforts have been put into increasing the yield and productivity of the biopolymer inside the bacteria. Equally important is the efficient extraction method to get them. Currently, an extraction method that is both rapid and non-detrimental to the product i.e. mcl-PHA is not available. In this study, a method to achieve the said goal was investigated through the application of ultrasound-assisted process. In addition, a combination of acetone as solvent and heptane as marginal non-solvent was used as the extraction medium. The effects of volumetric energy dissipation, extraction medium ratio and irradiation time on the extraction process were investigated. Frequency of 37 kHz and heptane as marginal nonsolvent facilitated the process. Following optimization, high PHA extraction rate of 74 10-3g PHA g-1 dried biomass min-1 was observed at ultrasonic energy output, solvent–marginal nonsolvent ratio and irradiation time of 1151 ± 3 J ml-1, 50:50 and 5 min respectively. The effects of exposure duration and ultrasonic power output on mcl-PHA solution in acetone were also studied. Molecular weight and thermal properties of ultrasound-irradiated mcl-PHA was characterized and compared to control (non- III irradiated mcl-PHA). It was found that at constant volumetric acoustic energy dissipation, prolonged exposure of up to 20 minutes caused slightly significant degradation of mcl-PHA. Under ultrasonic irradiation, degradation mechanism of mcl-PHA was proposed to involve random -chain scission. It proceeds via cleavage of ester linkage at the main chain backbone to form alkenyl terminal. In a related study, mcl-PHA produced by Pseudomonas putida Bet001 was used as a blending component with scl-PHA produced by Delftia tsuruhatensis Bet002. The thermal stability and film morphology of the blend between the brittle homopolymer polyhydroxybutyrate (scl-PHA) and flexible heteropolymer polyhydroxyoctanoate (mcl-PHA) were studied. The blends were prepared via film casting method and analyzed by differential scanning calorimetry (DSC), Field emmision scanning electron microscopy (FESEM), X-ray diffraction (XRD) and thermogravimetric analysis (TGA). The blend compositions were varied from 0, 25, 50, and 75 % (w/w) of mcl-PHA. The blends showed immiscibility with a morphology that constitutes of crystallite and amorphous phases. Formation of crystallite was observed from the XRD results. Despite the immiscibility, the thermal stability was improved for all blends.